2019
DOI: 10.1021/acs.jafc.9b02295
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Transcriptomic Analysis Reveals Regulatory Mechanisms of Theanine Synthesis in Tea (Camellia sinensis) and Oil Tea (Camellia oleifera) Plants

Abstract: Tea provides a rich taste and has healthy properties due to its variety of bioactive compounds, such as theanine, catechins, and caffeine. Theanine is the most abundant free amino acid (40%−70%) in tea leaves. Key genes related to theanine biosynthesis have been studied, but relatively little is known about the regulatory mechanisms of theanine accumulation in tea leaves. Herein, we analyzed theanine content in tea (Camellia sinensis) and oil tea (Camellia oleifera) and found it to be higher in the roots than … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 59 publications
0
15
0
Order By: Relevance
“…35 Until now, most of the studies on the theme of L-theanine metabolism in tea plants have been focused mainly on the genes involved in L-theanine synthesis and the possible transcription factors governing their transcription. 36,37 Few studies have investigated the role of L-theanine catabolism in Ltheanine accumulation and its regulatory mechanism in the developing tea plant or in response to biotic and abiotic stress.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…35 Until now, most of the studies on the theme of L-theanine metabolism in tea plants have been focused mainly on the genes involved in L-theanine synthesis and the possible transcription factors governing their transcription. 36,37 Few studies have investigated the role of L-theanine catabolism in Ltheanine accumulation and its regulatory mechanism in the developing tea plant or in response to biotic and abiotic stress.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…In addition to tea varieties, many other factors such as growing conditions, location, and harvest time could affect the l -theanine content accumulation in tea leaves. Matsuura and Kakuda in 1990 found that illumination and temperature strongly affected l -theanine accumulation in tea callus . Until now, most of the studies on the theme of l -theanine metabolism in tea plants have been focused mainly on the genes involved in l -theanine synthesis and the possible transcription factors governing their transcription. , Few studies have investigated the role of l -theanine catabolism in l -theanine accumulation and its regulatory mechanism in the developing tea plant or in response to biotic and abiotic stress. It has been reported that PDX2 in Arabidopsis could be regulated by high light, chilling, drought, and ozone .…”
Section: Resultsmentioning
confidence: 99%
“…The first way is based on the motif prediction of 2000 bp promoter sequence upstream of TS1 to find the possible gene families . The second way is to choose TFs with a rational correlation threshold in the gene coexpression network. , The promoter analysis based on known TFs-motif evidence is limited because of the completeness of the TFs–motif relationship collected in the related databases, such as PlantCARE and JASPAR . For example, there is no report on the binding motif of AtLBD38 , although it can inhibit the expression of AtGS1.4 in A.…”
Section: Discussionmentioning
confidence: 99%
“…61 The second way is to choose TFs with a rational correlation threshold in the gene coexpression network. 41,61 The promoter analysis based on known TFsmotif evidence is limited because of the completeness of the TFs−motif relationship collected in the related databases, such as PlantCARE 62 and JASPAR. 63 For example, there is no report on the binding motif of AtLBD38, although it can inhibit the expression of AtGS1.4 in A. thaliana.…”
Section: Identification Of Tarm and Its Gene Constitutionmentioning
confidence: 99%
“…The mechanism of accumulation of theanine in tender shoots of albino tea plants has not been well elucidated. Although theanine is synthesized in most tissues, it is significantly higher in young buds and roots of tea. , Agronomic practices also contribute to the synthesis of theanine. Shading increases theanine contents and decreases epicatechin and epigallocatechin contents, thus producing high-quality green tea …”
Section: Introductionmentioning
confidence: 99%